Dampak Pandemi Covid 19 terhadap Zakat Fitrah di Kota Pagar Alam - Imam Subhi; Risdianto Risdianto; Zulki Firnanda; Renaldi Akbar (Universitas Wahid Hasyim Semarang, 2021)
The covid 19 pandemic in Indonesia has been more than 1 year and 4 months epidemic and it is still going to worried rate as data released by the covid 19 task force stated that on July 17, 2021, the data was confirmed positive for 2,780,803, 2,204,491 people recovered and 71.397 people died. the number of pandemic is still going to grow in thousands. The impact of covid-19 is felt in all aspects of human life, one of which is with worship activities such as the implementation of zakat fitrah as regularly carried out every month of Ramadan. Pagar Alam town, based on this problem, the study used a descriptive qualitative approach, by taking samples of zakat management at the Nurul Huda mosque and the Raudlatul Jannah mosque. To obtain accurate and valid data, data collection techniques were used in the form of observation, interviews and documentation. The results stated that there was an impact caused by the Covid 19 pandemic, namely a decrease in number of muzakki (people who pay zakat) and mustahiq (people who receive zakat) in 2020, however, In 2021 will increase to stable. it happens in related to government policies such as applying new normal for Indonesian People.